Tourism and recreation as therapy for people with obesity - Piatnica, Katarzyna (Who needs tourism?, 2024)
Obesity is one of the chronic diseases. It is a major problem not only for health but also for society. Problems associated with obesity not only contribute to the development of various health complications, but also have negative consequences on quality of life and well-being. There are many forms of tourism and recreation that can be used to help treat obesity and offset its psychosocial effects. Therapeutic forms of tourism and recreation can contribute both to improving physical fitness and circulation, as well as lowering body weight, but can also significantly improve mood, raise self-esteem and thus restore a sense of being a full member of society. The study used a survey method which covered those struggling with obesity. In the light of the research, there seems to be a lack of education regarding the therapeutic value of tourism and recreation. The study showed that such people are mostly unaware of the benefits that can come from practicing dedicated forms of tourism and recreation.